Expert system for the identification and control of weeds in wheat crop - Islam, Shahnawazul; Sharma, R.K.; Chhokar, R.S.; Dhar, Shiva; Sabir, Naved; Chaturvedi, K.K.; Singh, Randhir; Farooqi, Mohd. Samir; Sharma, Kirti (Annals of Agricultural Research, 2017)
Effective weed management is important for a successful wheat production. Inadequate weed control can lead to significant yield loss and harvest problems. One of the pre-requisite of efficient weed management is proper weed identification so that suitable strategies are selected. An Expert System on Wheat Crop Management has been developed by ICAR-IASRI, New Delhi with the collaboration of ICAR-IARI, New Delhi, ICAR-IIDWR. Karnal and ICAR-NCIPM, New Delhi. This system has a crop protection module that carries a sub module on weed management. The module helps in identifying weeds and suggests treatment to minimize the production loss. The system carries information of about 23 major weeds affecting wheat crop and its management stored in its knowledge base. The system works as an information bank for wheat growing farmers that can help them in better crop management in order to enhance productivity and production of wheat in the country. The system is available at the URL http://www.iasri.res.in/wheat